Identification of Biomarker in Brain-specific Gene Regulatory Network Using Structural Controllability Analysis - Chen, Zhihua; Chen, Siyuan; Qiang, Xiaoli (Frontiers in Bioinformatics, 2022)
Brain tumor research has been stapled for human health while brain network research is crucial for us to understand brain activity. Here the structural controllability theory is applied to study three human brain-specific gene regulatory networks, including forebrain gene regulatory network, hindbrain gene regulatory network and neuron associated cells cancer related gene regulatory network, whose nodes are neural genes and the edges represent the gene expression regulation among the genes. The nodes are classified into two classes: critical nodes and ordinary nodes, based on the change of the number of driver nodes upon its removal. Eight topological properties(out-degree DO, in-degree DI, degree D, betweenness B